2020
DOI: 10.1186/s12935-020-01649-2
|View full text |Cite
|
Sign up to set email alerts
|

ETS1-activated SNHG10 exerts oncogenic functions in glioma via targeting miR-532-3p/FBXL19 axis

Abstract: Background In past few years, long non-coding RNAs (lncRNAs) have been reported to play regulatory roles during cancer progression. LncRNA SNHG10 has been explored in several sorts of cancers. However, its detailed role and mechanism are still not well understood in glioma. Methods Expression levels of genes were evaluated by RT-qPCR. EdU, TUNEL, sphere formation, wound healing and transwell assays appraised the effect of SNHG10 on glioma cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…miR-532-3p was predicted as a target miRNA of circNRIP1, which was confirmed by dual-luciferase reporter assays. Of note, miR-532-3p has been recognized as a tumor suppressor gene in several types of human cancer ( 30 – 32 ). Analysis of the TCGA dataset and in vitro results of the present study indicated that miR-532-3p was significantly downregulated in CRC tumor tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…miR-532-3p was predicted as a target miRNA of circNRIP1, which was confirmed by dual-luciferase reporter assays. Of note, miR-532-3p has been recognized as a tumor suppressor gene in several types of human cancer ( 30 – 32 ). Analysis of the TCGA dataset and in vitro results of the present study indicated that miR-532-3p was significantly downregulated in CRC tumor tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that lncRNAs could play as trans regulators scaffolds [ 7 ] or microRNAs sponges [ 8 ]. LncRNA SNHG10 has been reported dual-faced effects on cancer progress via different microRNAs in different human tumor [ 18 , 37 , 39 ]. SNHG10 was reported as oncogenic functions in glioma via targeting miR-532-3p/FBXL19 axis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SNHG10 has been reported dual-faced effects on cancer progress via different microRNAs in different human tumor [ 18 , 37 , 39 ]. SNHG10 was reported as oncogenic functions in glioma via targeting miR-532-3p/FBXL19 axis [ 39 ]. Meanwhile, in non-small cell lung cancer, SNHG10 was reported suppress cancer cell proliferation by upregulating tumor suppressive SIRT1 as miR-543 sponge [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of SNHG10 has been elucidated in various human cancers. For example, SNHG10 exerted oncogenic functions in glioma by sponging miR-532-3p and enhancing FBXL19 expression ( Jin et al, 2020 ). In addition, SNHG10 has reported to promote cell proliferation in osteosarcoma via increasing glucose uptake and miR-218 gene methylation ( He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%